The First Case of Kernohan-Woltman Notch Phenomenon Caused by Epidural Hematoma in a Pediatric Patient - Ozturk, Sait; Ozturk, Yasar; Ocal, Ozgur (Karger, 2017)
Kernohan-Woltman notch phenomenon ( KWNP) is an ipsilateral motor weakness due to compression of the contralateral cerebral peduncle. Most of the KWNP cases reported have been due to subdural hematomas, intracranial space-occupying lesions, and spontaneous bleeding of vascular malformations. In this study, we present the first pediatric case of KWNP caused by a traumatic epidural hematoma. Although subdural hematomas are the most frequent rea-son for KWNP, epidural hematomas may cause paradoxical ipsilateral signs not only in adults but also in pediatric patients. (C) 2017 S. Karger AG, Basel
Keywords: Kernohan-Woltman notch phenomenon; Epidural hematoma; Pediatric